Reliability of a VO2-derived running-speed threshold in trained men - Marialaura Espaillat; David M. Falkins; Brandi Antonio; David H. Fukuda; Jeffrey R. Stout (Journal of the International Society of Sports Nutrition)
Background This study aimed to establish the test-retest reliability of a VO2-derived running-speed threshold (RSVO2) in trained men.Methods Fourteen aerobically trained males (20.6 ± 1.9 y; 69.4 ± 10.2 kg; 176.1 ± 7.1 cm; VO₂peak 50.5 ± 7.8 mL·kg−1 ·min−1; time-to-exhaustion 27.5 ± 6.9 min) performed a graded-exercise test (start = 8 km·h−1, 0% grade; +1 km·h−1 every 3 min) to establish VO₂peak. During two subsequent visits, they completed four 8-min steady-state runs at 60, 70, 80, and 90% of final GXT speed, presented in random order. Minute-by-minute VO₂ from minutes 4–8 was averaged. The rate of VO₂ rise (ΔVO₂/Δt) was regressed against speed; the y-intercept at slope = 0 defined RSVO₂. Reliability statistics included ICC(2,1), standard error of measurement (SEM), coefficient of variation (CV), and minimal detectable change at 95% confidence (MDC95).Results RSVO₂ showed excellent reliability: ICC(2,1) = 0.96 (95% CI 0.89–0.99); SEM = 0.35 km·h−1; CV = 3.0%; MDC95 = 0.98 km·h−1. Threshold values did not differ between visits (p = 0.33). RSVO2 thresholds occurred at an average of 72.6% of the top stage completed during the GXT.Conclusions An eight-minute, multi-intensity protocol yields a highly reliable VO₂-based running-speed threshold in trained men. Future research should validate RSVO₂ against ventilatory and lactate thresholds and examine its applicability across sexes and clinical populations.